Recognize and Understand Occupational Safety Injuries Due to Heat or Fire Exposure in Industrial Homes: Kenali dan Pahami Keselamatan Kerja Cidera Akibat Paparan Panas atau Api di Home Industri - Shalahuddin, Iwan; Rosidin, Udin (Universitas Lancang Kuning, 2024)
The implementation of occupational safety and health (K3) aims to create a safe, comfortable, and healthy workplace. So that work accidents and consequences of occupational diseases can be prevented and work productivity increases, especially in controlling the risk of heat and fire exposure.The purpose of this service activity is: to increase awareness and knowledge of Tansu home industry owners and employees about the importance of work safety and healthy living behaviors. The methods carried out in health education are explanations or lectures, questions and answers and demonstrations through videos given by speakers to workers and owners of Home Industries. As a result of the activity, the participants of this activity were owners or owners of the home industry and 4 employees from the home industry with the result that there was an increase in knowledge with their ability to answer questions properly and correctly. Conclusion: There needs to be an effort to raise awareness about the importance of health in the workplace, including policies that support lifestyles